Hubungan Pendampingan Suami Dengan Tingkat Kecemasan Ibu Bersalin Di RS Umi Barokah Kabupaten Boyolali - Hapsari Tri Utami; Yuyun Triani (Journal of Educational Innovation and Public Health, 2023)
Background: Childbirth is a physiological process experienced by a woman in the final period of pregnancy which is followed by physiological and psychological changes. Mothers who experience anxiety during labour will significantly affect the delivery process. From several studies regarding the experiences of mothers who were accompanied by their husbands during childbirth, mothers felt that their husbands' presence was very helpful and made a special impression. Research Objectives: To determine the relationship between husband assistance and the anxiety level of mothers giving birth at Umi Barokah Hospital, Boyolali Regency. Research Method: This research is an observational analytic with a cross sectional approach. The sampling technique used is nonprobability sampling with incidental sampling method. The sample was calculated using the Slovin formula, namely 49 mothers who were accompanied or not accompanied by their husbands during childbirth. Data analysis used was the Chi Square test. Results: Of the 32 respondents who were accompanied by their husbands, 21 people (65.6%) experienced mild anxiety, while 11 people (64.7%) of the 17 respondents who were not accompanied by their husbands experienced moderate anxiety. The results of data analysis showed that there was a relationship between husband's assistance and the level of anxiety among women giving birth at Umi Barokah Hospital, Boyolali Regency with p-value = 0.006. Conclusion: There is a relationship between husband's assistance with the anxiety level of mothers giving birth at Umi Barokah Hospital, Boyolali Regency.